PENGARUH PENGGUNAAN APLIKASI WORDWALL DAN KAHOOT TERHADAP KEMAMPUAN PENALARAN MATEMATIS BERBASIS ETNOMATEMATIKA - Abdul Razaky Irani; Minta Ito Simamora; Nur Rahmi Rizqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of using Wordwall and Kahoot applications on ethnomathematics-based mathematical reasoning abilities. The research was conducted at SMP Negeri 29 Medan in the 2025–2026 academic year using a pretest-posttest control group design. The population consisted of 60 seventh-grade students, and a saturated sampling technique was applied, resulting in two classes: class VII-6 (30 students) as experimental class 1 and class VII-7 (30 students) as experimental class 2. The instrument used was a mathematical reasoning ability test in the form of pretest and posttest. Descriptive analysis showed that the average posttest score of experimental class 1 was 80.4, while experimental class 2 was 77.7. Prerequisite tests indicated that the data were normally distributed and homogeneous. The Independent Sample t-test showed a significance value of 0.008 < 0.05, indicating a significant effect of using Wordwall and Kahoot on students’ ethnomathematics-based mathematical reasoning abilities.